Evaluation of biologically mediated changes in oil sands naphthenic acid composition by Chlamydomonas reinhardtii using negative‐ion electrospray orbitrap mass spectrometry. Issue 4 (12th July 2014) - Goff, Kira L.; Peru, Kerry; Wilson, Kenneth E.; Headley, John V.; Graham, L.
<x xml:space="preserve">Abstract</x> Industrial activity associated with oil‐sands extraction in Canada's Athabasca region produces a variety of contaminants of concern, including naphthenic acid fraction components (NAFCs). NAFCs are a complex mixture of organic compounds that are poorly understood both in terms of their chemical composition and effects on the environment. NAFC toxicity in the unicellular green algae Chlamydomonas reinhardtii P.A.Dangeard was correlated with the presence of the algal cell wall. It was suggested that the toxicity of NAFCs in C. reinhardtii was due to surfactant effects. Surfactant‐cell wall interactions are specific and governed by the compound class and structure, and by the nature of the biological material. Here, we investigate the effects of wildtype (WT) C. reinhardtii and two cell‐wall mutants on specific classes of NAFCs when growing cultures were treated with a 100 mg · L−1 solution of NAFCs. Changes in the NAFC composition in the media were examined using high resolution mass spectrometry over a period of 4 d. Algal mediated changes in the NAFCs were limited to specific classes of NAFCs. In particular, the removal of large, classical naphthenic acids, with a double bond equivalent of 8, was observed in WT C. reinhardtii cultures. The observed algal mediated changes in NAFC composition would have been masked by low resolution mass spectrometry and highlight the importance of this tool in examining bioremediation of complex mixtures of NAFCs.